Assessing comparative terrestrial ecotoxicity of Cd, Co, Cu, Ni, Pb, and Zn: The influence of aging and emission source. (November 2015) - Owsianiak, Mikołaj; Holm, Peter E.; Fantke, Peter; Christiansen, Karen S.; Borggaard, Ole K.; Hauschild, Michael Z.
Abstract: Metal exposure to terrestrial organisms is influenced by the reactivity of the solid-phase metal pool. This reactivity is thought to depend on the type of emission source, on aging mechanisms that are active in the soil, and on ambient conditions. Our work shows, that when controlling for soil pH or soil organic carbon, emission source occasionally has an effect on reactivity of Cd, Co, Cu, Ni, Pb and Zn emitted from various anthropogenic sources followed by aging in the soil from a few years to two centuries. The uncertainties in estimating the age prevent definitive conclusions about the influence of aging time on the reactivity of metals from anthropogenic sources in soils. Thus, for calculating comparative toxicity potentials of man-made metal contaminations in soils, we recommend using time-horizon independent accessibility factors derived from source-specific reactive fractions. Graphical abstract: Highlights: We found an effect of source on reactivity of anthropogenic metals in soils. The influence of aging on reactivity of anthropogenic metals was not consistent. We recommend including source and disregarding aging in calculation of CTPs values. Abstract : Improving current life cycle inventory (LCI) and life cycle impact assessment (LCIA) practice in terrestrial ecotoxicity assessment of metals.